PELATIHAN MANAJEMEN USAHA DAN SOLIALISASI ALAT PEMISAH BIJI SIRSAK PADA KELOMPOK UMKM “TANI HASIL KEBUN” DI PATUK, GUNUNGKIDUL - Muhammad Priya Permana; Supriyanto, Sidiq (Universitas Mataram, 2024)
Kapanewon Patuk is a part of Gunungkidul district which has great potential in cultivating soursop fruit. People have been selling products directly to traditional markets. So the sale of soursop fruit is IDR 4,000/kg, making a small income. To overcome this problem, a community service program is proposed that focuses on HR management training and socialization of production using a soursop seed separator for the MSME group